New Uropodine mites from Tanzania (Acari: Mesostigmata) - Kontschán, Jenő; Starý, Josef (Zootaxa, 2013)
Three new species and one new genus of Uropodina from Tanzania are described and illustrated. They include the second species of the genus Bloszykiella Kontschán, 2010, Bloszykiella grebennikovi sp. nov., and the resurrection and re-defini-tion of the genus Spinosissuropoda Hirschmann, 1979, with description of a new species, Spinosissuropoda tanzanica sp. nov. Five species of Uropoda are transferred into the genus Spinosissuropoda – S. solarissima (Hirschmann, 1981) comb. nov., S. ancoraesimilis (Hirschmann, 1981) comb. nov., S. pocsi (Hirschmann, 1981) comb. nov., S. ancorae (Hirschmann, 1981) comb. nov. and S. alata (Hirschmann, 1981) comb. nov. A new monotypic genus, Afrodinychus gen. nov., is described and compared with the related genus Metadinychus Berlese, 1916.